2012
DOI: 10.1590/s0004-282x2012005000010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental encephalitis caused by Taenia crassiceps cysticerci in mice

Abstract: OBJECTIVES: To present the experimental model of neurocysticercosis (NCC) caused by Taenia crassiceps cysticerci, to describe the inflammatory process, susceptibility, or resistance of BALB/c and C57BL/6 mice to this infection, and to describe the host-parasite relationship. METHODS: The animals were intracranially inoculated with initial stage T. crassiceps cysticerci. They were euthanized at 7, 30, 60, and 90 days after the inoculation. Their encephala were removed for the histopathologic analysis, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 26 publications
(30 reference statements)
5
38
0
Order By: Relevance
“…The intracranial infection of the animals was performed as described by Matos-Silva et al 6 . Briefly, the animals were weighed and anesthetized with 0.01ml/g of ketamine 10% and xilazine 2% intraperitoneal injection.…”
Section: Experimental Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The intracranial infection of the animals was performed as described by Matos-Silva et al 6 . Briefly, the animals were weighed and anesthetized with 0.01ml/g of ketamine 10% and xilazine 2% intraperitoneal injection.…”
Section: Experimental Infectionmentioning
confidence: 99%
“…The NCC symptoms are caused by the host inflammatory response, immune response modulation, location of the parasite, evolutionary stage of the parasite, parasitic burden, as well as the mass effect induced by its growth, which results in a wide clinical and laboratory polymorphism challenging the diagnosis of this disease 3,4 . Experimental models have been used as important tools in the study and comprehension of the host-parasite relationship in human cysticercosis in several locations including the neurological one 5,6,7 . The most-used parasite in the experimental models is Taenia crassiceps cysticercus due to its rapid development cycle and its antigenic similarity with T. solium 7,8 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Also in this Issue, Matos-Silva et al 26 , from Federal University of Goiás, report the development of an experimental model to NC studies involving two mice lineages by using T. crassiceps cysticerci. The authors observed in this original study that C57BL/6 mice showed greater capability on provoking early necrosis in the cysticerci with a chronic inflammation pattern, while BALB/c mice showed necrosis on late stage parasites with an acute inflammation pattern.…”
Section: Referencesmentioning
confidence: 99%